(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Insurance and Automobile Industries are growing sector with distinctive products and services in India. At present, the industries taxes have been changed and formulated by Indian government as Goods and Service Tax (GST). Goods and Services tax is considered to be an important tax reform in the country. Goods and Services tax is based on destination principle which means tax accrues at the place of consumption rather than the place of manufacturing. Common people are more affected by the goods and services tax and the effects were adverse at the time of introduction of goods and services tax. Tirupur District is fairly populated area and containing more textile work employees in Tamilnadu State. The researcher has collected primary data from 100 sample respondents from July 2017 to November 2017. The convenient sampling method has been used for choosing the sample size and the present study. The study also analyses the effect of GST on the buying behaviours changes of customers and it has examined that the influences of the GST concept in Tirupur District. Such an analysis is likely to be helpful for providing the idea about effectiveness of GST initiation in Indian economy. The present study has focused on the customer’s problems and clear perception on GST system in Tirupur district. The selected respondents are paying GST for products and services in various places and business concern in selected study area. This present study provides that actual position and condition on the basis of demographic factors and their perception on GST tax system in Tirupur District. The present study helps to recommend the changes in current GST tax slabs in our developing country.